Symmetries and Fundamental Interactions in Nuclei - Haxton Wick C. (World Scientific, 1995)
This text shows the usefulness of the nucleus as a laboratory for learning about basic symmetries and fundamental interactions. Aimed at advanced graduate students and beginning researchers, it should also be useful to advanced researchers in the field of nuclear and particle physics.